The Issues of Nation-Building in Nepal - Mallik, Sabita Kumar (Kutumbha vani, 2024)
This article presents the issues of nation-building in Nepal. It reflects the multi-cultural, multi-ethnic, multi-religious, multi-lingual society and the conflicts based on their diversity, which are the major issues of nation-building. The data, statistical facts and historical evidences are collected from viable and authentic resources of the study. The qualitative method of study is the primary focus of the research. In order to reach conclusions, nationbuilding also applies customs, religions, and culture. Descriptive and analytical methods have been employed in this process. Nepal has been struggling with inequality which is the great barrier in nation-building. This article tries to address the major areas of inequalities in Nepal and the reasons behind it. It also focus on the proper management of these conflicts or inequalities, so that the diverse groups of people should be brought in the main stream of nation building which is the major need of various nations at present.